Assaults on Days of Campaign Rallies During the 2016 US Presidential Election. Issue 4 (July 2018) - Morrison, Christopher N.; Ukert, Benjamin; Palumbo, Aimee; Dong, Beidi; Jacoby, Sara F.; Wiebe, Douglas J.
Abstract : Background: This study investigates whether assault frequency increased on days and in cities where candidates Donald Trump and Hillary Clinton held campaign rallies prior to the 2016 US Presidential election. Methods: We calculated city-level counts of police-reported assaults for 31 rallies for Donald Trump and 38 rallies for Hillary Clinton. Negative binomial models estimated the assault incidence on rally days (day 0) relative to that on eight control days for the same city (days -28, -21, -14, -7, +7, +14, +21, and +28). Results: Cities experienced an increase in assaults (incidence rate ratio [IRR] = 1.12, 95% CI: 1.03–1.22) on the days of Donald Trump's rallies, and no change in assaults on the days of Hillary Clinton's rallies (IRR = 1.00; 95% CI: 0.94–1.06). Conclusion: Assaults increased on days when cities hosted Donald Trump's rallies during the 2016 Presidential election campaign. Abstract : Supplemental Digital Content is available in the text.